2017
DOI: 10.1371/journal.pone.0185999
|View full text |Cite|
|
Sign up to set email alerts
|

Nanoparticle curcumin ameliorates experimental colitis via modulation of gut microbiota and induction of regulatory T cells

Abstract: Background and AimsCurcumin is a hydrophobic polyphenol derived from turmeric, a traditional Indian spice. Curcumin exhibits various biological functions, but its clinical application is limited due to its poor absorbability after oral administration. A newly developed nanoparticle curcumin shows improved absorbability in vivo. In this study, we examined the effects of nanoparticle curcumin (named Theracurmin) on experimental colitis in mice.MethodsBALB/c mice were fed with 3% dextran sulfate sodium (DSS) in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
118
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(122 citation statements)
references
References 39 publications
(63 reference statements)
1
118
0
3
Order By: Relevance
“…[15] Earlier studies also demonstrated that treatment with Curcumin or dietary polyphenols causes alterations in microbial composition accompanied by induction of mucosal immune cells. [6,43,48,49] Our current data also demonstrate that administration of ETO-Cur-TRF modulates fecal microbial composition and increases microbial OTU biodiversity.…”
Section: Plos Onesupporting
confidence: 69%
“…[15] Earlier studies also demonstrated that treatment with Curcumin or dietary polyphenols causes alterations in microbial composition accompanied by induction of mucosal immune cells. [6,43,48,49] Our current data also demonstrate that administration of ETO-Cur-TRF modulates fecal microbial composition and increases microbial OTU biodiversity.…”
Section: Plos Onesupporting
confidence: 69%
“…Recently, we developed a nanotechnology-based delivery system for curcumin which uses lecithin, a vegetable-based phospholipid that is a major component of all cell membranes [11]. This active nanosphere, when loaded with curcumin, designated as CN, has the ability to improve the aqueous-phase solubility and bioavailability, showing many biological functions in gastrointestinal epithelial cells and in the mouse gut [12,13]. While CN has been shown to have attractive therapeutic efficiency in gastrointestinal diseases, its role in the pathogenesis of a Gram-negative V. vulnificus infection remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Positive results of these studies led to the development of Phase II trials for chemoprevention of colon cancer [25]. Another study investigated the effect of nanoparticle curcumin on colitis in mice by modulating intestinal microflora and induction of regulatory T cells [26]. Nanoparticle curcumin inhibited mRNA expression on the mucosa of inflammatory mediators and activation of NF-κB in colon epithelial cells.…”
Section: The Effect Of Curcumin On the Gut Microbiotamentioning
confidence: 99%
“…Nanoparticle curcumin inhibited mRNA expression on the mucosa of inflammatory mediators and activation of NF-κB in colon epithelial cells. These effects were accompanied by an increase in butyrate-producing bacteria and fecal butyrate levels [26]. Therefore, the authors concluded that supplementation with curcumin nanoparticles induced a remission of colitis by modulating the structure of the intestinal microflora [26].…”
Section: The Effect Of Curcumin On the Gut Microbiotamentioning
confidence: 99%